Effects of metallic dust on Nile tilapia: Exploring the relationship between metal bioaccumulation, metallothionein levels, and oxidative stress responses - Maraschi, Anieli Cristina; Adorno, Henrique Aio [UNESP]; Gonçalves, Yan Costa [UNESP]; Souza, Iara Costa; Monferrán, Magdalena Victoria; Wunderlin, Daniel Alberto; Fernandes, Marisa Narciso; Monteiro, Diana Amaral (Elsevier, 2024)
Settleable atmospheric particulate matter (SePM), from steelmaking processes, contains a complex mixture of metals, metalloids, and metallic nanoparticles. The SePM is released airborne and disperses in water, representing a significant threat to aquatic life, particularly fish. This study investigated the effects of a sublethal and environmentally relevant concentration of SePM (1 g·L−1) for 96 h in the gill, liver, kidney, and white muscle of Nile tilapia (Oreochromis niloticus), employing exposure and effect biomarkers to test causality between metal accumulation and biochemical responses. The gills and liver showed the highest bioaccumulation of metals and integrated response index value, indicating susceptibility to metal accumulation. However, the gills produce a protective mucus layer that may mitigate metal toxicity. The kidneys and muscle tissue also showed bioaccumulation of metals, although to a lesser extent. The liver and kidneys experienced oxidative stress, characterized by reduced metallothionein and glutathione levels, as well as damage to lipids, proteins, and DNA. The accumulation of less-studied metals, particularly Rare Earth Elements (REEs), compromised the integrity of biomolecules in these tissues. In conclusion, the complex dynamics of metal bioaccumulation in Nile tilapia exposed to SePM reveal varied tissue responses and primary effects like oxidative damage. They also highlight the need for further research and regulation of other metals and their potential impacts on aquatic ecosystems and human health.
Keywords: Atmospheric particulate matter; Biomarkers; Fish; Metal bioaccumulation; Oxidative stress